2017
DOI: 10.1111/josh.12507
|View full text |Cite
|
Sign up to set email alerts
|

Improving School Experiences for Adolescents With Type 1 Diabetes

Abstract: Implications for school health including specifics for school nurses, teachers, students, and school environment were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 55 publications
3
47
1
8
Order By: Relevance
“…It is important to note that the sensor usage time in this group of patients was high, which allowed for the proper functioning of the SmartGuard technology. On the other hand, adolescents are especially prone to difficult management which altogether results in a lower quality of life and deteriorates glycemic control . However in our study we were able to achieve high compliance to PLGS.…”
Section: Discussioncontrasting
confidence: 47%
“…It is important to note that the sensor usage time in this group of patients was high, which allowed for the proper functioning of the SmartGuard technology. On the other hand, adolescents are especially prone to difficult management which altogether results in a lower quality of life and deteriorates glycemic control . However in our study we were able to achieve high compliance to PLGS.…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore all teachers participating in this study reported lack of academic education regarding management of school children with chronic illnesses, and several of the teachers reported not receiving any formal training or education in the workplace, even though the number of children with chronic illnesses in school increased (Diamond Project Group, 2006;Patterson et al, 2009). Lack of education for school personnel regarding T1DM has been shown in earlier studies (Boden et al, 2012;Clay et al, 2004;Hinton and Kirk, 2015;Kise et al, 2017;Marschilok et al, 2011;Moore et al, 2009;Olson et al, 2004;Wodrich et al, 2011) and should be considered as an area in need of development. Most teachers regarded the healthcare provider as vital for diabetes education, but at the same time as inflexible, hard to reach, and with limited resources (for example to visit schools).…”
Section: Education For Teachersmentioning
confidence: 75%
“…Furthermore, earlier research found a positive environment important for youth with T1DM to feel safe and included, as well as effective collaboration and communication between child, parent and school (Kise et al, 2017;Marschilok et al, 2011), whereas poor communication between teachers and students with chronic illnesses was found to be major barrier for adequate support (Boden et al, 2012;Hinton and Kirk, 2015).…”
Section: Trusting Relationships With Teachersmentioning
confidence: 98%
“…These problems and shortcomings could on the one hand burden parents, who feel anxious about the safety of their children and are forced to be responsible for their care even during school hours, and on the other hand could lead to negative experiences for diabetic students. School rules are sometimes inflexible thus hindering self-care of diabetes [4,6]. In a study conducted by Wang et al Taiwanese adolescents with T1DM admitted that teachers often thought signs and symptoms related with high or low levels of blood glucose to be excuses for absences or disobedience [21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these recommendations, several previous studies have shown that parents raise concerns regarding the safety of their diabetic children at school [4][5][6] and that teachers in different educational stages are not knowledgeable enough about the disease and its management [7][8][9][10][11][12][13][14][15]. The aim of our study was to assess the knowledge and attitudes of nursery school, preschool and primary school teachers about diabetes and its management in the school setting in Greece.…”
Section: Introductionmentioning
confidence: 99%